The Effect of Gross Profit Margin, Intellectual Capital, Investment Opportunity Set on Firm Value with Earnings Management as an Intervening Variable - Andrianto, Andrianto; Amin, Aminul (International Journal Labs, 2023)
Firm value is indicated to be influenced by several factors such as gross profit margin, intellectual capital, investment opportunity set, and earnings management. This study aims to determine the effect of gross profit margin, intellectual capital, and investment opportunity set either directly or indirectly through earnings management on firm value. This study used a sample of food and beverage companies listed on the IDX for the period 2017-2021 totaling eighteen companies. The study used secondary data with time series and cross-section panel data. The sample selection was carried out by purposive sampling. The analysis technique used to test the hypothesis is path analysis. The quantitative approach was used in this study, with multiple linear regression analysis tools and using the SPSS 22 program. The results showed that partially gross profit margin affects earnings management. Intellectual capital affects earnings management. Investment opportunity set has no effect on earnings management. Gross profit margin affects firm value. Intellectual capital has no effect on firm value. Investment opportunity set affects firm value. Earnings management has no effect on firm value. Indirectly gross profit margin on firm value through earnings management the results have no effect. Indirectly intellectual capital on firm value through earnings management has no effect. Indirectly investment opportunity set on firm value through earnings management has no effect. This study provides information on factors that affect firm value and adds empirical evidence related to earnings management as an intervening variable.